Extraction and purification of lipoxygenase of local chicken meat (Journal of the College of Basic Education, 2022)
The study included selecting the best method for extracting lipoxygenase enzyme from local chicken meat, out of eight methods, and sodium chloride (10%) was the best in extracting the enzyme with a total efficiency of (918810) units. The protein content was concentrated using ammonium sulfate (60)% among five concentration methods (partial purification), and the purification stages were completed using ion exchange and gel filtration on a DEAE - Sephadex-A50 column, and then using a sephacryl S - 300 gel filtration column. The specific activity is (17.10) units/ml, the total activity is (393) units, the enzymatic yield is (42.9)%, and the purification times are (7.50) times. Then, the purity of the enzyme was confirmed by conducting the electrophoresis process in the absence of protein denaturing materials